Data-driven optimization of the in silico design of ionic liquids as interfacial cell culture fluids - Jun Nakanishi; Takeshi Ueki; Sae Dieb; Hidenori Noguchi; Shota Yamamoto; Keitaro Sodeyama (Science and Technology of Advanced Materials)
As an alternative to conventional plastic dishes, the interface between water-immiscible hydrophobic fluids, such as perfluorocarbons and silicones, permits cell adhesion and growth. Thus, it is expected to replace the petroleum-derived products in a sustainable society. However, most hydrophobic fluids are cytotoxic, which limits the range of mechanical and chemical cues exposed to the cells. Using a data-driven approach, this study aimed to identify non-cytotoxic ionic liquids (ILs) as fluid culture platforms to take advantage of their ‘designer’ nature for broadening the possible physicochemical ranges exposed to cells and their repeated use owing to their high heat stability before their biological applications. The new candidates within the readily synthesized ammonium-type ILs were identified through the active cycle of regression and a limited number of cytotoxicity tests. Structure – cytotoxicity analysis indicated that the presence of multiple long alkyl branches was critical for low cytotoxicity. Particularly, we successfully cultured human mesenchymal stem cells (hMSCs) at the trihexylethylammonium trifluoromethylsulfonylimide interface and repeated their use after solvent extraction and heat sterilization. This study identified non-cytotoxic ILs that fulfill plastics’ 3 R (Reduce, Recycle, and Replace) requirements and opens new avenues for hMSC fate manipulation through mechanotransduction.